Pengaruh Work-life Balence Terhadap Dukungan Organisasi dan Kepuasan Kerja Karyawan Milenial: Studi Literatur - Rudy Stiawan; Prastyo Tri Hartono; Naila Afifah Khairi; Ryanti; Nadila Anjelina; Hardi Mulyono; Irma Idayati (ManBiz: Journal of Management and Business, 2025)
This study explores the influence of work-life balance on organizational support and job satisfaction of millennial employees. Work-life balance, which involves balancing professional and personal life, is increasingly important for millennials who prioritize flexibility at work. work. Through a literature review, this research identified three key components of work-life balance: time balance, engagement, and satisfaction. satisfaction. The results showed that organizational support can improve work-life balance and in turn contribute to job satisfaction. Employees who are satisfied with their work-life balance tend to show better performance and loyalty to the organization. This research recommends that companies develop policies that policies that support work-life balance to improve productivity and employee satisfaction